Current Treatments for Patients with Genetic Obesity - Nathan Faccioli; Christine Poitou; Karine Clément; Béatrice Dubern (Galenos Yayincilik, 2023)
Obesity derives from impaired central control of body weight, implying interaction between environment and an individual genetic predisposition. Genetic obesities, including monogenic and syndromic obesities, are rare and complex neuro-endocrine pathologies where the genetic contribution is predominant. Severe and early-onset obesity with eating disorders associated with frequent comorbidities make these diseases challenging. Their current estimated prevalence of 5-10% in severely obese children is probably underestimated due to the limited access to genetic diagnosis. A central alteration of hypothalamic regulation of weight implies that the leptin-melanocortin pathway is responsible for the symptoms. The management of genetic obesity has so far been only based, above all, on lifestyle intervention, especially regarding nutrition and physical activity. New therapeutic options have emerged in the last years for these patients, raising great hope to manage their complex situation and improve quality of life. Implementation of genetic diagnosis in clinical practice is thus of paramount importance to allow individualized care. This review describes the current clinical management of genetic obesity and the evidence on which it is based. Some insights will also be provided into new therapies under evaluation.